PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA ORGANISASI DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI - Dewi Kusuma Wardani; Anita Primastiwi; Nur Hasna (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2021)
This study was aimed to reveal whether budgetary participation in student activity units (UKM) in UST had an effect on organizational performance through motivation. This research data uses direct / primary data. The sampling method is convenience sampling. The data analysis technique is path analysis, where budgetary participation becomes the independent variable and organizational performance becomes the dependent variable, and motivation becomes the moderating variable. The results of the analysis conclude that budgeting participation has a positive effect on organizational motivation and performance, motivation also has a positive effect on organizational performance, and budget participation also has a positive effect on organizational performance through motivation. The implication of this research proves that participation in budgeting is one of the elements that has an important role in the growth of organizational performance within members of the student activity unit (UKM).